Development and Validation of a Fast and Homogeneous Cell-Based Fluorescence Screening Assay for Divalent Metal Transporter 1 (DMT1/SLC11A2) Using the FLIPR Tetra. (July 2014) - Montalbetti, Nicolas; Simonin, Alexandre; Dalghi, Marianela G.; Kovacs, Gergely; Hediger, Matthias A.
Divalent metal ion transporter 1 (DMT1) is a proton-coupled Fe 2+ transporter that is essential for iron uptake in enterocytes and for transferrin-associated endosomal iron transport in many other cell types. DMT1 dysfunction is associated with several diseases such as iron overload disorders and neurodegenerative diseases. The main objective of the present work is to develop and validate a fluorescence-based screening assay for DMT1 modulators. We found that Fe 2+ or Cd 2+ influx could be reliably monitored in calcium 5–loaded DMT1-expressing HEK293 cells using the FLIPR Tetra fluorescence microplate reader. DMT1-mediated metal transport shows saturation kinetics depending on the extracellular substrate concentration, with a K0.5 value of 1.4 µM and 3.5 µM for Fe 2+ and Cd 2+, respectively. In addition, Cd 2+ was used as a substrate for DMT1, and we find a Ki value of 2.1 µM for a compound (2-(3-carbamimidoylsulfanylmethyl-benzyl)-isothiourea) belonging to the benzylisothioureas family, which has been identified as a DMT1 inhibitor. The optimized screening method using this compound as a reference demonstrated a Z′ factor of 0.51. In summary, we developed and validated a sensitive and reproducible cell-based fluorescence assay suitable for the identification of compounds that specifically modulate DMT1 transport activity.